SPECTRUM OF CHEST X-RAY FINDINGS IN COVID-19 POSITIVE PATIENTS UTILIZING MODIFIED RALE SCORE FOR SEVERITY ASSESSMENT - Atiq-Ur-Rehman Slehria (Army Medical College Rawalpindi, 2020)
Objective: To assess chest x-ray appearance of patients with positive RT-PCR test for SARS-Cov-2 and utilize modified RALE score for severity assessment of chest x-ray findings for correlation with clinical spectrum of disease.